Are Currency Crises Predictable? A Test - Pattillo, Catherine A. (International Monetary Fund, 1998)
This paper evaluates three models for predicting currency crises that were proposed before 1997. The idea is to answer the question: if we had been using these models in late 1996, how well armed would we have been to predict the Asian crisis? The results are mixed but somewhat encouraging. One model, and our modifications to it, provide useful forecasts, at least compared with a naive benchmark. The head-to-head comparison also sheds light on the economics of currency crises, the nature of the Asian crisis, and issues in the empirical modeling of currency crises